FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN BPJS DALAM PELAYANAN KEPERAWATAN DI RUANGAN RAWAT INAP KELAS III RSUD ROKAN HULU - Rinancy, Hariet; Yurustin, Devina (Universitas Pahlawan, 2021)
Patient satisfaction is an important indicator that must be considered in health services. Patient satisfaction is the result of the patient's assessment of health services by comparing what is expected in accordance with the reality of health services received in a hospital health setting. The aim of this research is to determine the factors related to patient satisfaction in the Internal Medicine Poly Room at Bangkinang Regional Hospital. This type of research is analytical with a cross sectional design. The population in this study were all outpatients who visited the Internal Medicine Clinic at Bangkinang District Hospital from January to March 2021, totaling 423 with a sample of 81 people, the sampling technique used side incidentals. The data collection tool in this research is using a questionnaire. Data analysis in this study used univariate and bivariate analysis. The results of statistical tests show that there is a relationship between the availability and services of specialist doctors, the availability and services of nurses, waiting times and service opening hours with patient satisfaction. It is hoped that this research can be used as reference material for further research because there are many other factors that cause patient dissatisfaction at Bangkinang District Hospital and for the hospital in the future it can provide more optimal services for patients.